Development of E-Module on Regulary System Material for Class XI High School - Ananda, Cherly Novika; Yanti, Febri; Hidayat, Yosmed (RADINKA JAYA UTAMA PUBLISHER, 2022)
The purpose of this research is to produce an e-module product that is feasible and valid as an alternative teaching material for students. This study uses the 4D development method which consists of 4 stages, namely define, design, develop, and dessiminate. The findings of this study are succeeded in developing an e-module on material system regulation for class XI SMA. Based on the results of the validation questionnaire that has been carried out with Lecturers and Teachers, the average score is 90.1% with very valid criteria. Thus, the developed e-module is said to be valid for use by students.